Assessing bone mineral density in children and adolescents living with HIV and on treatment with tenofovir disoproxil fumarate: a systematic review - Maria Brennda Ferreira de Gusmão; Vinícius Vital de Oliveira; Natália Maria da Silva Santos; Luciana Costa Melo (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To investigate the impact of tenofovir disoproxil fumarate on bone mineral density and bone mineral content in children and adolescents infected with the human immunodeficiency virus. Data source: The search procedure was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement. The search was carried out until April 2022 in Medical Literature Analysis and Retrieval System Online (Medline), Embase, Cochrane Central, Latin American and Caribbean Health Sciences Literature, Web of Science, Scopus, and MedRxiv. The combination of terms used was: (Children OR Youth OR Teenagers) AND HIV AND (Tenofovir OR "Antiretroviral therapy") AND ("Bone density" OR Osteoporosis OR Osteopenia). The protocol was registered in the International Prospective Register of Systematic Reviews (PROSPERO, CRD42022312851) Data synthesis: The initial searches resulted in 1156 papers. After the exclusion of duplicate studies, three blinded reviewers analyzed the title and abstract of 563 papers, of which 57 remained to be read in full. Only nine papers met the eligibility criteria and were included in descriptive and risk-of-bias analyses. Regarding study design, four were cross-sectional, three were longitudinal before-after studies without a control group, and two were prospective cohorts. Among these nine papers, seven showed no significant association between tenofovir disoproxil fumarate use and reduced bone mass in young people. However, these papers did not have high methodological quality. Conclusions: Although most of the selected papers found no harmful effect of tenofovir disoproxil fumarate on bone mass, further primary research with higher methodological quality is needed so robust scientific evidences can be obtained.